All Days 2000
DOI: 10.2118/59753-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Permeability Gas Reservoirs and Formation Damage -Tricks and Traps

Abstract: I-.cI8d for pr8SeIII81kxI by ~ SPE PIIvwn CamiII8e foIow8Ig r8'Iiew It .mmaIkIrI ca1C8I8d In .. ab8act SID'*Ied by VIe aullCW(s).CQIII8* It VIe peper,-, '-rd b.-I ~ by VIe SocIety of PeInJIeI8n EIvr-. n-~ 10 The Traps!! When addressing the potential productivity of the low permeability gas reservoir, three major issues are of paramount concern. 1. Does the reservoir exhibit sufficient initial permeability and pressure to facilitate economic gas production rates, even in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The core was then flooded with a mixture of 75% n-decane (nC 10 ) and 25% n-hexadecane (nC 16 ) to displace the liquid remaining in the core, followed with isopropyl alcohol (IPA) to clean out adsorbed chemicals. However, the continuously decreased permeability indicates that the chemical solutions did not solve the problem.…”
Section: Verendrye Core #23mentioning
confidence: 99%
See 1 more Smart Citation
“…The core was then flooded with a mixture of 75% n-decane (nC 10 ) and 25% n-hexadecane (nC 16 ) to displace the liquid remaining in the core, followed with isopropyl alcohol (IPA) to clean out adsorbed chemicals. However, the continuously decreased permeability indicates that the chemical solutions did not solve the problem.…”
Section: Verendrye Core #23mentioning
confidence: 99%
“…At this point liquid carbon dioxide was injected through the core since it is known to have some affinity to water (16) . Surprisingly, the permeability of the core rose to 4.3×10 -3 µm 2 , which is even slightly higher than the original brine permeability.…”
Section: Verendrye Core #23mentioning
confidence: 99%
“…Water-based fracturing fluids are commonly used to fracture tight reservoirs in North America (Wasylishen and Fulton, 2012), and it has been reported that only 5% to 50% of the injected fluid is typically recovered as "flowback" (Zelenev and Ellena, 2009). Water loss to the formation can have detrimental effects on the hydrocarbon flow from chemical and mechanical damage, for example clay swelling or rock softening (Alramahi and Sundberg, 2012;Das et al, 2014;Zhang et al, 2015), to relative permeability damage due to capillary trapping of the water phase and water blocking (Abrams and Vinegar, 1985;Bennion et al, 2000;Dutta et al, 2014;Kamath and Laroche, 2003;Mahadevan and Sharma, 2005;Liang et al, Submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, supplementing fracturing fluids with surfactants that reduce capillary trapping of water has been recognized as a potential solution to permeability damage due to water blocks (Bennion et al, 2000). Several studies have investigated the use of surfactant-based fluid additives to enhance flowback and regain matrix gas permeability (Penny and Pursley, 2007;Rostami and Nasr-El-Din, 2014;Zelenev and Ellena, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential mechanism of damage is from capillary trapping of water near the fracture face. Water trapping in tight formations has been studied in the past (Bennion et al, 1996) and permeability damage due to water blocking has been documented (Abrams and Vinegar, 1985;Bennion et al, 2000;Tannich, 1975).…”
Section: Introductionmentioning
confidence: 99%